Is microbiological control of the box tree moth feasible? Effectiveness and impact on non-target diurnal Lepidoptera - Francesca Barbero; Cristina Pogolotti; Simona Bonelli; Chiara Ferracini (Biological Control)
Recent outbreaks of the invasive alien species Cydalima perspectalis (Walker, 1859) (Lepidoptera: Crambidae) have led to the widespread loss of boxwoods in Europe. Although details on its biology are not fully unraveled, the box tree moth (BTM) can be considered a major pest, severely damaging its primary host, Buxus sempervirens, ultimately affecting the associated coenosis. In European environments, box trees form the Habitat 5110, and BTM outbreaks are seriously endangering its long-term survival.The effectiveness of microbiological treatments with Bacillus thuringiensis var. kurstaki (Btk) on the survival of BTM was evaluated in field and controlled conditions. Given the scant specificity of Btk action, an in-depth survey of its potential impact on non-target diurnal Lepidoptera has been conducted by monitoring their communities’ changes in treated and control areas.Btk spraying was highly effective in the field, and five days after treatments larval density reduction was over 90% in all sites and years, with similar mortality trends achieved in controlled conditions.No significant short-term effects were detected either on non-target diurnal lepidopterans’ abundance or species richness.These results can be combined with the outcomes of spatially explicit models to overcome issues that, up to now, have caused the failure of appropriate strategies to control C. perspectalis. Even if no impact has been observed on non-target Lepidoptera, a rigorous plan for the application, detection and surveillance of the potential effects of microbiological treatments needs to be established.